Two cases of achalasia (mega-oesophagus), secondary to encephalitis - İnce, Lâtife; Özbay, Neclâ; Oto, Nuri (The Turkish Journal of Pediatrics, 1971)
In the light of our two cases and the review of the medical literature in the pathogenesis of achalasia, a lesion of the brainstem or of the dorsal nucleus of the vagus and its preganglionic fiber may be a cause of motor disturbance of the entire oesophagus, as much as a lesion of the Auerbach’s plexus itself.Therefore we believe that our two cases of achalasia secondary to encephalitis confirm this observation.